Stress response in tomato as influenced by repeated waterlogging - Umićević, Sonja; Kukavica, Biljana; Maksimović, Ivana; Gašić, Uroš; Milutinović, Milica; Antić, Marina; Mišić, Danijela (Frontiers in Plant Science, 2024)
Introduction Plants respond to water stress with a variety of physiological and biochemical changes, but their response varies among species, varieties and cultivars. Waterlogging in tomato reduces plant growth, degrade chlorophyll and increase concentration of oxidative parameters. Priming can alleviate stress in plants caused by waterlogging enabling plants to be more tolerant to an additional stress in the current or even subsequent generation. The aim of this study was to evaluate tomato genotypes for their sensitivity to waterlogging stress applied during early vegetative growth and at full flowering stage. Materials and methods The study included two local genotypes, Trebinjski sitni (GB1126) and Žuti (GB1129), and the reference variety Novosadski jabučar (NJ), which is the variety most commonly used in Serbia and Bosnia and Herzegovina. The activity of class III peroxidase (POX), hydrogen peroxide (H2O2) content and malondialdehyde (MDA) content were measured spectrophotometrically, and for quantification of individual phenolic compounds, targeted approach was adopted, using UHPLC/DAD/(-)HESI-MS2 instrument (Dionex UltiMate 3000 UHPLC system with a DAD detector, configured with a triple quadrupole mass spectrometer TSQ Quantum Access Max (Thermo Fisher Scientific, Germany)). Results and discussion Oxidative parameters (H2O2 and MDA) exhibited an increase in content in leaves of tomato plants that underwent waterlogging stress compared to control plants. Moreover, oxidative parameters showed positive correlation with proteins and phenolics content. The obtained correlations can indicate that one of the response strategies of tomato plants to waterlogging is the increased synthesis of proteins and phenolic compounds. The POX activity was not correlated with other parameters except with the polyphenols. A positive correlation was shown between POX activity and the content of phenolic compounds, indicating their independent roles in the removal of ROS. Changes in the phenolic profiles after the exposure of plants to waterlogging stress are recorded, and these changes were more severe in leaves and fruits of GB1129 and NJ genotypes than in GB1126. Thus, genotype GB1126 is the most efficient in maintaining the phenolic profiles of leaves and fruits, and therefore of the nutritive and organoleptic qualities of fruits following the exposure to waterlogging. Also, genotype GB1126 exhibited the ability to maintain the content of oxidative parameters during waterlogging at certain growth stages, implying certain waterlogging tolerance. Conclusion Waterlogging triggered stress memory but not at all growth stages. The most pronounced stress memory was obtained in fruit samples in the phase of full fruit maturity on the 1st truss. This study shed light on the defense mechanisms of tomato plants to repeated waterlogging stress from the perspectives of the changes in the composition of major phenolics, and pointed to the 5-O-caffeoylquinic acid and rutin as the chemical markers of the waterlogging stress tolerance in tomato. However, it remains to be determined whether this modulation has a positive or negative effect on the overall plant metabolism. Further investigations are needed to fully elucidate the benefits of waterlogging pretreatment in this context.